(untitled) (AYUSHDHARA, 2025)
Ayurveda, the ancient Indian system of medicine, adopts a holistic perspective on health, emphasizing the balanced integration of body, mind, and spirit. Among its major disciplines, Bhaishajya Kalpana (Ayurvedic pharmaceutics) is concerned with the formulation, preparation, and quality assurance of medicinal products. Within this field, Churna Kalpana refers to herbal formulations in powdered form, which are widely appreciated for their ease of administration, fast absorption, and long shelf life. In Ayurvedic understanding, Krimi Roga encompasses diseases caused by internal and external parasites, often resulting from unclean habits, poor dietary choices, and lifestyle imbalances. To manage such conditions, classical texts recommend Vidangadi Churna- a traditional polyherbal preparation, with Vidanga (Embelia ribes) as its principal component. This formulation includes herbs with Krimighna (antiparasitic), Deepana (digestive stimulant), and Pachana (carminative) properties, aimed at eradicating intestinal parasites, strengthening digestive fire (Agni), and preventing recurrence. By supporting detoxification and enhancing digestive function, Vidangadi Churna showcases the therapeutic potential of Ayurvedic interventions in managing parasitic disorders. Scientific validation and standardization of such classical formulations can enhance their credibility and set the stage for their integration into modern evidence-based healthcare systems.